PENDIDIKAN BERMASYARAKAT MODEL NABI MUHAMMAD SEBAGAI SOLUSI ALTERNATIF KEHIDUPAN BERMASYARAKAT DI INDONESIA - Gunawan Efendi (Educreative : Jurnal Pendidikan Kreativitas Anak, 2020)
The model of community education in the form of the prophet Muhammad is community education modeled on the ways of education carried out by the prophet Muhammad SAW. Among the models of the prophet Muhammad SAW education. namely the development of Islamic education, curriculum, materials, methods, institutions, guidance during the time of the Prophet Muhammad SAW. Alternative solutions for social life in Indonesia include Indonesian education that must be designed in such a way as to enable students to develop their potential naturally and creatively in an atmosphere of freedom, togetherness, and responsibility. In addition, education must produce graduates who can understand their community with all the factors that can support success or obstacles that cause failure in social life. One alternative that can be done is to develop an education model of the Prophet Muhammad SAW.